H∞ Consensus for Discrete-Time Multiagent Systems - Xiaoping Wang; Jinliang Shao (Discrete Dynamics in Nature and Society)
An H∞ consensus problem of multiagent systems is studied by introducing disturbances into the systems. Based on H∞ control theory and consensus theory, a condition is derived to guarantee the systems both reach consensus and have a certain H∞ property. Finally, an example is worked out to demonstrate the effectiveness of the theoretical results.